Measuring Sovereign Risk: Are CDS Spreads Better than Sovereign Credit Ratings?. Issue 1 (11th May 2018) - Rodríguez, Iván M.; Dandapani, Krishnan; Lawrence, Edward R.
Abstract: Using data for 54 countries over a 12‐year period, we find that the variation in average sovereign ratings in a given year can be explained by average credit default swap (CDS) spreads over the previous three years. In a horse race between CDS spreads and sovereign ratings, we find that CDS spread changes can predict sovereign events, while rating changes cannot. The predictability of CDS spreads is greater when there is disagreement between Moody's and the S&P for a country's rating.